The IgM isotype of anti-annexin A5 antibodies and multiple positivity of conventional antiphospholipid antibodies: increasing the number of clinical manifestations of primary antiphospholipid syndrome. Issue 5 (May 2016) - Bećarević, Mirjana; Stojanović, Ljudmila; Ignjatović, Svetlana; Dopsaj, Violeta
Abstract We evaluated the importance of anti-annexin A5 antibodies (aanxA5 Abs) for clinical (thrombosis and/or recurrent pregnancy loss) and serologic (presence of antiphospholipid antibodies: lupus anticoagulant (LA), anticardiolipin (aCL), and anti-β2 glycoprotein I (aβ2GPI) antibodies) features of patients with primary antiphospholipid syndrome (PAPS). Our study included 70 patients with PAPS according to the international consensus criteria for APS. The mean age of the analyzed patients was 45.97 ± 12.72. The disease duration above 5 years was present in 31/70 of patients. Concentrations of analyzed antibodies were measured by ELISA. Cutoff values were set in accordance to the manufacturers' recommendations. History of recurrent pregnancy loss was associated with double positivity for aanxA5 IgM and LA (χ 2 = 4.000, P = 0.046) and triple positivity for aanxA5 IgM + LA + aβ2GPI IgM (χ 2 = 4.168, P = 0.041). Venous thromboses were associated with triple positivity for aanxA5 IgM + aCLIgG + aβ2GPI IgM (χ 2 = 3.965, P = 0.046). The IgG isotype of aanxA5 Abs was in positive correlation with aCL Abs of the IgG (r = 0.310, P = 0.009) and IgM (r = 0.254, P = 0.034) isotype. The presence of the clinical manifestations of PAPS is increasing with the number of positive conventional aPL and the IgM aanxA5 Abs tests. This new combination of Abs is beneficial even when the number of patients with positivity for aanxA5 Abs is low. This is important in further detection of patients prone to recurrence of thrombotic episodes.